JURIDICAL REVIEW OF THE CRIMINAL ACT OF ASSAULT COMMITTED DUE TO MOMENTARY EMOTION IN DECISION NUMBER 2057/PID/2025/PN.MDN - Robbi Rusmandiar; Syahrul Bakti Harahap (Jurnal Ilmu Hukum dan Keadilan, 2026)
committed due to momentary emotional impulse under Article 351 paragraph (1) of the Indonesian Criminal Code, to examine the legal reasoning of the judges in imposing criminal sanctions from the perspective of evidentiary aspects and principles of criminal law, and to analyze the implementation of the principle of proportionality in sentencing in Decision Number 2057/PID/2025/PT.MDN in relation to modern theories of punishment. The type of research employed is normative legal research using statutory and conceptual approaches, relying on primary legal materials in the form of court decisions and legislation, as well as secondary legal materials consisting of doctrines developed by criminal law scholars.The results of the research indicate that the elements of the criminal offense of assault in the a quo case have been legally and convincingly fulfilled, and that momentary emotional impulse does not eliminate the defendant’s guilt or criminal responsibility, but merely serves as a mitigating factor. The judges’ legal reasoning in imposing the sentence was based on valid evidence and the application of the principles of legality, culpability, justice, and individualization of punishment. Furthermore, the application of the principle of proportionality in sentencing is reflected in the imposition of a penalty that does not reach the maximum statutory threat and takes into account the defendant’s subjective circumstances, thereby aligning with modern theories of punishment and contributing to the effectiveness of criminal law enforcement.